Avaliação da influência da temperatura de moagem do clínquer e do tempo de armazenamento do cimento em silos no comportamento da falsa pega do cimento portland CPI-S - Mota, Roger Machado (2019)
Portland cement is a hydraulic binder obtained by grinding Portland clinker with the addition of one or two forms of calcium sulfate during the production process. The standard Portland cement with addition (CPI-S), besides the raw materials quoted before, has an addition of 6 to 10% of mass to be processed in cement grinding of carbonate material containing at least 75% CaCO3. In the cement grinding stage gypsum is added to the clinker for the purpose to delay the reaction hydration of tricalcium aluminate (C3A), that is the constituent of the clinker features the biggest reactivity with water, with the basic function of controlling the cement setting time. Besides the cement setting, another behavior that stands out in the CPI-S cement is the false setting, when cement stiffens prematurely in a few minutes after adding water. Some variables could cause false setting on the CPI-S Portland cement, among them cement storage time in silos and the clinker milling or cement temperature. The temperature increases cause calcium sulfate dihydrate to dehydrate, forming hemihydrate (CaSO4.0.5H2O) or anhydrite (CaSO4), which causes the false setting. In this study, the influence of clinker milling temperature (100, 105, 110, 120 and 130°C) and the cement storage time in silo (30, 60 and 120 min) was studied regarding CPI-S false setting behavior. Physicochemical analysis, TG/DTG, XRF, and XRD were applied as complementary analyses for the false setting of CPI-S assays. It was verified that temperatures above 110°C and cement storage above 60 min of CPI-S are conditions that favor the false setting of CPI-S.